2003
DOI: 10.1007/s10295-002-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the growth and yield of Pleurotus ostreatus mushroom on different lignocellulosic by-products

Abstract: Eight lignocellulosic by-products were evaluated as substrates for cultivation of the oyster mushroom, Pleurotus ostreatus ( Jacq. ex. fr) Kummer. The yields of mushroom on the different substrates were 183.1, 151.8, 111.5, 87.8, 49.5, 23.3, 13.0 and 0.0 g for composted sawdust of Triplochiton scleroxylon, rice straw, banana leaves, maize stover, corn husk, rice husk, fresh sawdust, and elephant grass, respectively. The biological efficiency (BE) followed the same pattern and ranged from 61.0% for composted sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
3
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 4 publications
14
88
3
5
Order By: Relevance
“…Both strains of P. geesteranus (PG1 and PG3) exhibited slowest primordia emergence. Obodai et al (2003) reported that pinhead formation took four to six days after the completion of spawn running, with harvest after 10 to 12 days in the case of P. ostreatus on different substrate, in the climatic conditions of Pakistan. Strain PHK also produced the highest number of primordia, followed by strains PG1 and PG3, whereas the lowest number of primordia per 500 g per bag was produced by PO2 and PO3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both strains of P. geesteranus (PG1 and PG3) exhibited slowest primordia emergence. Obodai et al (2003) reported that pinhead formation took four to six days after the completion of spawn running, with harvest after 10 to 12 days in the case of P. ostreatus on different substrate, in the climatic conditions of Pakistan. Strain PHK also produced the highest number of primordia, followed by strains PG1 and PG3, whereas the lowest number of primordia per 500 g per bag was produced by PO2 and PO3.…”
Section: Resultsmentioning
confidence: 99%
“…Amin et al (2007a) and Sarker et al (2007b) found similar yield for P. ostreatus. However, Obodai et al (2003) reported a biological efficiency ranging from 61 to 0% for P. ostreatus. This could be due to the different substrate formulations and strain variations.…”
Section: Resultsmentioning
confidence: 99%
“…However, 25 species out of these are considered to be intensively cultivated commercially (Hussein et al, 2015). Among the 25 species of mushroom, oyster mushroom ranks the third world wide (Obodai et al, 2003). The process of mushroom cultivation has lot of advantages such as that, it utilises little land for production, which renders them economically beneficial (Dzomeku, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional procedure for this mushroom's cultivation is to use pasteurized compost steam (Molena, 1986;Obodai et al, 2003). On the other hand, these mushrooms exhibit great versatility and fast colonization rates, so several alternative cultivation techniques have been proposed.…”
Section: Medicinal Mushroom (Agaricus Brasiliensis)mentioning
confidence: 99%